Fine Structure Intervals ‎ ‎-‎ ‎ , ‎ ‎-‎ ‎ and ‎Electric Dipole Transition Rate ‎ ‎-‎ ‎ in ‎Phosphorus Isoelectronic Sequence ‎ ‎ ‎And Phosphorus Ions (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
A systematic study for the calculation of the fine structure intervals -  and -   for the ground configuration 3s23p3 and the excited configuration 3s23p24s respectively, and electric dipole transition rate -  as well as transition energy form the excited configuration 3s23p24s to the ground configuration 3s23p3 in Phosphorus isoelectronic sequence by applying multi-configuration Dirac-Fock (MCDF) method. The effect of Breit interaction, QED and correlation on the fine structure interval and the gauge invariance effect on the transition probability are studied. Also the fine structure intervals for the phosphorus ions from Piii to Pxv are calculated and are compared with the available experimental data and gives good consistent